1991
DOI: 10.1159/000235508
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Leukotriene Involvement in Pulmonary Eosinophil Migration upon Antigen Challenge in the Actively Sensitized Guinea Pig

Abstract: Male Dunkin Hartley guinea pigs, actively sensitized to ovalbumin (OA) and pretreated with mepyramine (1 mg/kg i.p.), were challenged with OA as an aerosol. Histological analysis of the lung for eosinophils (EOs) showed significant accumulations in the submucosa of the airways (8 h: 1,477.3 ± 43 EOs/mm2 airway, n = 3, p < 0.01), after antigen challenge compared to saline control (478.6 ± 104 EOs/mm2 airway, n = 4). Pretreatment with both mepyramine and cimetidine (10 mg/kg i.p.) did not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 17 publications
5
28
0
Order By: Relevance
“…Similar results were obtained with LTC 4 or LTD 4 in guinea pigs (Foster and Chan, 1991;Underwood et al, 1996), with single administration of inhaled LTD 4 elicited a marked increase in eosinophils, which was maintained for at least 4 weeks (Underwood et al, 1996). The receptor responsible for this phenomenon of the cys-LTs appears to be CysLT 1 receptor (Foster and Chan, 1991;Underwood et al, 1996) and, at least in guinea pigs, appeared to involve IL-5 (Underwood et al, 1996), a key cytokine in eosinophil proliferation, activation, and survival. Pobilukast inhibited LTD 4 -induced chemotaxis of peripheral blood eosinophils from nonasthmatic volunteers (Spada et al, 1994).…”
Section: Diverse Effects Of Cysteinyl-leukotrienessupporting
confidence: 75%
See 2 more Smart Citations
“…Similar results were obtained with LTC 4 or LTD 4 in guinea pigs (Foster and Chan, 1991;Underwood et al, 1996), with single administration of inhaled LTD 4 elicited a marked increase in eosinophils, which was maintained for at least 4 weeks (Underwood et al, 1996). The receptor responsible for this phenomenon of the cys-LTs appears to be CysLT 1 receptor (Foster and Chan, 1991;Underwood et al, 1996) and, at least in guinea pigs, appeared to involve IL-5 (Underwood et al, 1996), a key cytokine in eosinophil proliferation, activation, and survival. Pobilukast inhibited LTD 4 -induced chemotaxis of peripheral blood eosinophils from nonasthmatic volunteers (Spada et al, 1994).…”
Section: Diverse Effects Of Cysteinyl-leukotrienessupporting
confidence: 75%
“…For example, inhaled LTE 4 (Laitinen et al, 1993) or LTD 4 selectively increased airway eosinophil numbers when assessed in bronchoalveolar lavage from humans (Smith et al, 1993). Similar results were obtained with LTC 4 or LTD 4 in guinea pigs (Foster and Chan, 1991;Underwood et al, 1996), with single administration of inhaled LTD 4 elicited a marked increase in eosinophils, which was maintained for at least 4 weeks (Underwood et al, 1996). The receptor responsible for this phenomenon of the cys-LTs appears to be CysLT 1 receptor (Foster and Chan, 1991;Underwood et al, 1996) and, at least in guinea pigs, appeared to involve IL-5 (Underwood et al, 1996), a key cytokine in eosinophil proliferation, activation, and survival.…”
Section: Diverse Effects Of Cysteinyl-leukotrienessupporting
confidence: 67%
See 1 more Smart Citation
“…LTC 4 and LTD 4 induce a dose-dependent infiltration of eosinophils into the guinea-pig lung, which can be blocked by cys-LT-receptor antagonists [23]. LTD 4 induces both early-and late-phase allergen-induced bronchoconstriction in sheep of the dual-responder type [12], but this phenomenon was not found in humans [24].…”
Section: Discussionmentioning
confidence: 93%
“…We found that nasal LTD4, but not histamine, challenge induced significant eosinophil infiltration into guinea pigs that persisted until 24 hr after LTD4 challenge. It has been reported that LTD4 (30 yg/ml) inhalation caused prolonged eosinophil infiltra tion into guinea pig lungs (15,16). These results collec tively suggest that LTD4 potently induces eosinophil infiltration.…”
Section: Discussionmentioning
confidence: 99%